Management model to optimize the administration and management of resources of regional governments in accordance with the framework law of modernization of state management - Chenguayen Rospigliosi, Juan Antonio (2017)
The objective was to formulate a management model to optimize the management and administration of resources in regional governments. The design was not experimental. The study sample was constituted by 30 officials of the regional governments. A questionnaire and a data collection form were used, constructed and validated for the purposes of the study. Among the main results, it was found that the perception of the managerial role deployed in regional governments is outdated and does not contribute to governance (53.3%) and that it is a priority as part of the organizational design (46.7%); and the main reasons that would not allow an adequate execution of the resources is to prevail political interests (33.3%) and unmotivated personnel (26.7%). Conclusion: A management model is formulated to optimize the management and administration of resources in regional governments, with a new organizational approach.